Intake and Digestibility of Cattle’s Ration on Complete Feed Based-On Fermented Ammonization Rice Straw with Different Protein Level - Hamdi Mayulu; S. Sunarso; M. Christiyanto; F. Ballo (International Journal of Science and Engineering, 2013)
Complete feed (CF) utilization is expected to have impact on higher productivity due to increased intake and digestibility. The objective of research was to evaluate the effects of different level protein of CF based-on fermented ammonization (amofer) rice straw to Simmental offspring intake and digestibility  Twenty males Simmental offspring with average live weight 372.15± 26.64 kg (coefficient of variance 7.16%) were used in this study. Feed treatment consisted of BC Nutrifeed 132 concentrate as control feed (T0) and CF based-on amofer rice straw consisted of T1, T2, T3 and T4 which had crude protein content 11, 12, 13 and 14% respectively and also total digestible nutrients (TDN) ±  62%. Completely randomized design with five treatments and four replicates were designed for this research. Data was analyzed by analysis of variance (ANOVA) at 95% significance level. The results showed that different crude protein did not affect the intake of dry matter, organic matter, crude protein and TDN. It was significantly affected the digestibility of dry matter, organic matter and crude protein (p<0.01). The highest digestibility was obtained to treatment with 12% crude protein and ± 62% TDN. Conclusion of this study was different level of crude protein constituted in CF which produced from specific material resource was proven to have impact in increasing cattle’s digestibility.Doi: 10.12777/ijse.4.2.2013.86-91 [How to cite this article: Mayulu, H., Sunarso, S.,  Christiyanto, M. and Ballo, F. (2013). Intake and Digestibility of Cattle’s Ration On Complete Feed Based-On Fermented Ammonization Rice Straw  With Different Protein Level.  International Journal of  Science and Engineering, 4(2),86-91. Doi: 10.12777/ijse.4.2.2013.86-91]